Communicating About Precision Oncology - McFarland, Daniel C. (JCO Precis Oncol, 2017)
Communication in oncology has always been challenging. The new era of precision medicine complicates communication even further as a result of our increasing reliance on genomic data and the varying psychological responses to genomic-based treatments and their expected outcomes. The crux of the matter hinges on understanding communication. The informed consent process may require more attention in the precision medicine era. However, many of the communication issues are actually similar to perennial long-standing communication issues in oncology, which center on providing hope when breaking bad news and ensuring that adequate informed consent to treatments is obtained. This piece presents several common patient reactions to different precision medicine scenarios in oncology practice. We highlight these new communication issues that focus on clinical and ethical questions (ie, informed consent, shared decision making, patient autonomy, and uncertainty in oncologic treatments) and provide guidance on working with each scenario. In this article, we address common reactions of patients to genomic information and provide thoughtful communication suggestions using a Shared Decision Making framework to help patients cope with the inherent distress-provoking uncertainties in oncology practice.